PENGARUH PROMOSI PENJUALAN DAN CITRA MEREK TERHADAP NIAT BELIPRODUK YAMAHA NMAX(Studi Pada Komunitas Pemilik Sepeda Motor Premium Di Surabaya Pusat) - BAGUS PRASETYA, RISKI (Jurnal Ilmu Manajemen (JIM), 2016)
Yamaha Nmax scooter matic is newly issued in February 2015. Sales of Yamaha Nmax very rapidly even if the campaign carried out quite a bit and the brand image of Yamaha is still inferior to its competitors. This study aims to determine the sales promotion and brand image on purchase intentions the product yamaha Nmax Study on Community premium motorcycle owners in Surabaya. The population in this study is the community premium motorcycle in Surabaya of at least 19 years old. The total sample of 220 respondents with techniques sample by nonprobability sampling. There are some data collection techniques which is used in this research, those are questionnaire, literature study, interviews and data analysis techniques using multiple linear regression. The results of this studyis to indicate that the sales promotion and brand image influence significantly on purchase intention. Then. the rest is influenced by other variables outside the research. Keywords: Sales Promotion, Brand Image, and Purchase Intention<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />